2008
DOI: 10.1021/ac701999b
|View full text |Cite
|
Sign up to set email alerts
|

Protein Surface Mapping Using Diethylpyrocarbonate with Mass Spectrometric Detection

Abstract: The reliability and information content of diethylpyrocarbonate (DEPC) as a covalent probe of protein surface structure has been improved when used appropriately with mass spectrometric detection. Using myoglobin, cytochrome c, and β-2-microglobulin as model protein systems, we demonstrate for the first time that DEPC can modify Ser and Thr residues in addition to His and Tyr residues. This result expands the capability of DEPC as a structural probe because about 25% of the sequence of the average protein can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
230
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(243 citation statements)
references
References 38 publications
13
230
0
Order By: Relevance
“…The chemistry of these reagents varies such that a wide range of amino acid side chains can be probed providing structure assessment of proteins with single side chain resolution. [31][32][33][34][35][36][37][38][39] In particular, footprinting can be performed with either less-specific labels, such as hydroxyl radicals that can label more than 16 side chains or more specific labels that target a few particular residues. Because understanding how changes in formulation, alterations in post-translational modifications such as glycosylation, or other changes in the production of the protein influence the structure and thus its activity is crucial when developing therapeutic proteins, CL-based footprinting methods can provide quantitative assessments of tertiary and quaternary structure.…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of these reagents varies such that a wide range of amino acid side chains can be probed providing structure assessment of proteins with single side chain resolution. [31][32][33][34][35][36][37][38][39] In particular, footprinting can be performed with either less-specific labels, such as hydroxyl radicals that can label more than 16 side chains or more specific labels that target a few particular residues. Because understanding how changes in formulation, alterations in post-translational modifications such as glycosylation, or other changes in the production of the protein influence the structure and thus its activity is crucial when developing therapeutic proteins, CL-based footprinting methods can provide quantitative assessments of tertiary and quaternary structure.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Gross et al found that the number of exchangeable hydrogens decreases as the concentration of Ca 2ϩ is increased up to ϳ0.25 mM, which they interpret as a tightening of the Ca 2ϩ binding domains of calmodulin [43,44]. Reactive labeling groups can also be used to monitor protein surface structure [45]. Specific, noncovalent interactions with the side-chains of proteins can also be used to probe protein structure [46 -50].…”
mentioning
confidence: 99%
“…to probe Arg accessibility, and has been used to study the conformational transitions in LacY, in combination with diisopropyl carbodiimide labeling of carboxyl groups [241]. Diethylpyrocarbonate (DEPC) is also a commonly encountered modifying reagent, and whilst it primarily targets His it also has the potential to react with Lys, Arg, Tyr, Thr and Cys residues [242,243]. DEPC, along with all other covalent labels, is able to provide restraints for integrative modeling workflows, as exemplified in recent work on the F 0 F 1 ATPase from spinach chloroplasts (in combination with XL-MS data) [243].…”
Section: Other Chemical Labelling Methodsmentioning
confidence: 99%